Tumour growth inhibitory effect of Ibervillea sonorae phytopreparations in cervical cancer xenografts - Vidal-Gutiérrez, Max; Torres-Moreno, Heriberto; Arenas-Luna, Víctor M.; Loredo-Mendoza, María Lilia; Tejeda-Dominguez, Farid; Velazquez, Carlos; Vilegas, Wagner [UNESP]; Hernandez-Gutiérrez, Salomón; Robles-Zepeda, Ramón E. (Taylor & Francis, 2024)
Cucurbitacin IIb, a triterpene obtained from the Ibervillea sonorae plant, reduces tumour development in a preclinical model of cervical cancer. Acetison and Etanison, phytopreparations made from I. sonorae, present biological activity analogous to CIIb in HeLa. This research evaluated the tumour growth inhibitory effect of these phytopreparations in a HeLa xenograft tumour model in BALB/c nude mice. Tumours in mice were treated every 3 days for 12 days with cisplatin (2 mg/kg), CIIb (5 mg/kg), Acetison (20 mg/kg), Etanison (30 mg/kg), and DMSO at 2%. For histological observations, tumours were stained with H&E. Fingerprinting of both phytopreparations was performed using HPLC-UV and UHPLC-APCI-IT-MS. Both phytopreparations and CIIb inhibit tumour development as well as Cisplatin (75.5%); Etanison (77.7%), Acetison (73.6%), and CIIb (73.0%). Furthermore, only tumours treated with cisplatin showed invasion of bone tissue. The results show the potential use of I. sonorae phytopreparations in the treatment of cervical cancer.
Keywords: antitumoral effect; cucurbitacin; cucurbitacin IIb; Ibervillea sonorae; phytomedicine; phytopreparation